Alkyl decorated metal–organic frameworks for selective trapping of ethane from ethylene above ambient pressures. Issue 30 (9th July 2021) - Schneemann, Andreas; Jing, Yuan; Evans, Jack D.; Toyao, Takashi; Hijikata, Yuh; Kamiya, Yuichi; Shimizu, Ken-ichi; Burtch, Nicholas C.; Noro, Shin-ichiro
Abstract : The alkyl decorated MOF Zn2 (TM-bdc)2 (dabco) shows good adsorption selectivity towards ethane over ethylene, which was revealed by breakthrough, coadsorption and high pressure adsorption. Abstract : The trapping of paraffins is beneficial compared to selective olefin adsorption for adsorptive olefin purification from a process engineering point of view. Here we demonstrate the use of a series of Zn2 (X-bdc)2 (dabco) (where X-bdc 2− is bdc 2− = 1, 4-benzenedicarboxylate with substituting groups X, DM-bdc 2− = 2, 5-dimethyl-1, 4-benzenedicarboxylate or TM-bdc 2− = 2, 3, 5, 6-tetramethyl-1, 4-benzenedicarboxylate and dabco = diazabicyclo[2.2.2.]octane) metal–organic frameworks (MOFs) for the adsorptive removal of ethane from ethylene streams. The best performing material from this series is Zn2 (TM-bdc)2 (dabco) (DMOF-TM), which shows a high ethane uptake of 5.31 mmol g −1 at 110 kPa, with a good IAST selectivity of 1.88 towards ethane over ethylene. Through breakthrough measurements a high productivity of 13.1 L kg −1 per breakthrough is revealed with good reproducibility over five consecutive cycles. Molecular simulations show that the methyl groups of DMOF-TM are forming a van der Waals trap with the methylene groups from dabco, snuggly fitting the ethane. Further, rarely used high pressure coadsorption measurements, in pressure regimes that most scientific studies on hydrocarbon separation on MOFs ignore, reveal an increase in ethane capacity and selectivity for binary mixtures with increased pressures. The coadsorption measurements reveal good selectivity of 1.96 at 1000 kPa, which is verified also through IAST calculations up to 3000 kPa. This study overall showcases the opportunities that pore engineering by alkyl group incorporation and pressure increase offer to improve hydrocarbon separation in reticular materials.